Cultural alienation to contemporary societies and its relationship to mass culture from the perspective of McDonald's mass culture theory - بوطورة حنان; منصوري سميرة (International Journal of Social Communication, 2021)
The connotations of alienation have evolved throughout historical times to withstand different psychological or social connotations until today's era of globalization and cultural hegemony, linked to the consumer culture that modern communication technology promotes in contemporary societies, in a way that has created a cultural crisis in contemporary society and is embodied in the absence of effectiveness at the individual and social level, in the context of social liquidity, which is not stable in keeping with the ever-regenerating market and desires of modern man. We have concluded that mass consumer culture has caused many manifestations of cultural alienation in contemporary societies, such as the senseless, infinite and other dimensions that have been linked from the point of view of MacDonald's mass culture to the commodity culture that has collapsed with mass cultural taste by promoting a superficial culture through modern means of communication technology.